Online music store (oms) - Mohd Hafiz, Roslan (2013)
In the music industry, to find a comprehensive system that meets all requirements are difficult. There are not too many of them in the world that produced a system like that. This project is done to overcome the lack of features in the music website. Online Music Store (OMS) is a web based system that design to build a well-defined website that acts as a music database. This system includes three categories of users which are unregistered user, users that classified registered user and musician, and admin. The methodology uses for the website development is Rapid Application Development (RAD). In this project, the enhancement of features increases the user’s usability and creates a network among music enthusiastic.